Uma proposta de capacitação para elaboração de aulas de ciências inclusivas - Marçal, Suelen Estulano (2020)
Considering the educational politics that has been structured since the mid-twentieth century to promote an accessible study and adapted education for people with disabilities, this work have the intention of to develop a capacitation course for teachers or future teachers that prepares them for adapted science classes. So, has been constructed a schoolar material named: “Accessibility and Inclusion for Science Teaching” in handout composed by the chapters: The person with disabilities throughout history, The rights of people with disabilities in the Brazilian laws; General information (written about curriculum, assistive technology and physical disability); Adaptations for teaching science to students with hearing disability; Adaptations for teaching science to students with visually disability; and Adaptations for teaching science to students with learning difficulties. In this last chapter, has been included cognitive conditions that could complicate the teaching-learning process, like: Down syndrome, autism spectrum disorder, dyslexia and attention deficit disorder. To verify the viability of the course and the material developed, the product was applied to students in the last semester of graduation in Chemistry at the Federal University of Mato Grosso. The course lasted 16 hours, divided into 12 hours in person and 4 hours of extra-class activity to be do it throughout the course. To assess whether the product achieved the objective of this search, participants were asked to did an inclusive study plan using the knowledge acquired in the course. Among the 33 students enrolled, 5 (15%) didn’t show up any day of the course and 3 (9%) were only on 1 day. A total of 10 (30%) students didn’t make the requested study plan. Among those who made the study plan, 8 (24%) students presented study plans written by other persons, 3 (9%) being copied totally from the internet, 3 (9%) has been partial copies from the internet without mentioning the authors and 2 (6%) copied from colleagues. Among the other study plans without plagiarism, 7 (21%) didn’t have inclusion explanation, 2 (6%) presented confusing and no inclusion reasoning, and only 5 (15%) study plans has been written with didactic strategies that promoted inclusion. Considering the results obtained, we can infer that the low commitment and no interest of students in their training and in the importance of promote inclusion measures is a reflection of society who still needs expressive changes in their culture, so that people with disabilities or difficulties learning feel welcomed in educational institutions and have the same opportunities as other students.